A Study on Sex-Based Hematology and Biochemistry of Lesser Whistling Duck (Dendrocygna javanica) - Pranoto , Hendro; Nugrahalia, Meida (International Journal of Poultry Science, 2020)
Background and Objective:  Hematological and biochemical data are important physiological aspects that can be used as an initial strategy to assess, monitor and manage wildlife. Hematological and biochemical profiles are influenced byage, sex, postprandial, season, climatic conditions, reproductive status and diurnal changes.This study aimed to measure the hematological and biochemical parameters of Dendrocygna javanica based on its sex. Materials and Methods:  A total of 24 Dendrocygna javanica (12 male and 12 female) were captured from two different locations. Blood samples were taken using superficial metatarsal plantar. Meanwhile, the time lag between capture and blood sampling was 3 minutes to avoid physiological changes due to stress. The blood was taken as much as 1% of body weight using a 23 gauge needle. Samples were inputted to vacutainers, EDTA tubes, for hematological examination and non-additive vacutainer for biochemical examination. Statistical analysis of hematological and biochemical parameters between sexes was performed using a t-test with a 95% confidence level. Results:  The calculation results of erythrocytes, mean corpuscular volume (MCV), eosinophils, heterophils, lymphocytes, monocytes and the H/L ratio showed significant differences between males and females. Aspartate aminotransferase (AST) and glucose in males were higher than females (p<0.05). Conclusion:  Hematological and biochemical parameters in males tend to be higher than females.